Religion: a confounding cultural element in the international harmonization of accounting? - Hamid, Shaari; Craig, Russell; Clarke, Frank (Wiley Blackwell, 1993)
Discussion of the influence of culture on the international development and harmonization of accounting has focused primarily upon indigenous characteristics which are confined within national boundaries. But cultural inputs, such as religion, which transcend national boundaries, should not be overlooked. Islam is a particular case in point. Its principles commit Muslims to a definitive code of ethical commercial and personal behaviour affecting both the structuring and financing of business affairs between the faithful, and between Muslims and non‐Muslims. Islam has the potential for influencing the structure, underlying concepts and the mechanisms of accounting in the Islamic world. Its potential for influencing accounting policy is illustrative of religion as a confounding element in the analysis of national idiosyncrasies in accounting practice and in deconstructing the impediments to international harmonization.